Influence of Metformin Dose and Treatment Adherence on Glycemic Control, Adiposity, and Cardiovascular Risk Markers in Iraqi Patients with T2DM - Abdulrahman, Zainab; Alatrakji, Mohammed Qasim; Al-Maliky, Ahmed Abood; Hussein, Khalid Ibrahim; Hussain, Saad Abdulrahman (Journal of the Faculty of Medicine Baghdad, 2023)
Background: Numerous factors, including metformin doses and treatment adherence, may contribute to significant variations in glycemic control and adiposity markers of type 2 diabetes (T2DM) patients.Objectives : This study aims to determine the influence of metformin dose and treatment adherence on glycemic control and adiposity markers in Iraqi patients with T2DM.Methods: Between October 2021 and March 2022, a case-series study at the Diabetes and Endocrinology Center – Baghdad included 153 T2DM patients with a disease duration of more than one year. Clinical and physical examinations were conducted before enrolment. We measured anthropometric variables to calculate the body mass index (BMI), waist-to-hip ratio (WHR), visceral adiposity index (VAI), and other surrogate indicators. We measured glycated hemoglobin (HbA1c), leptin, C-reactive protein (CRP), total cholesterol, HDL-c, and triglycerides in the serum.Results: Increasing metformin doses did not improve the studied parameters. Adherence to treatment significantly influences fasting glycemia, HbA1c level, and the markers of adiposity. Meanwhile, increasing metformin doses is not associated with changes in insulin resistance and cardiovascular disease risk markers.Conclusion: Beyond metformin dose up-titration, treatment adherence affects glycemic control, visceral adiposity, and CVD risk surrogates. Metformin dose up-titration was not linked to insulin resistance and body fat contents.